HUBUNGAN PERAN ORANGTUA DENGAN PERILAKU SOPAN SANTUN ANAK USIA DINI DI TK KRISTEN GMIT KOINONIA KUPANG - Mundiarti, Vanida (Universitas Nusa Cendana, 2022)
This research is motivated by the role of parents in education for children, especially in children's polite behavior. This study aims to determine whether there is a relationship between the role of parents and the polite behavior of early childhood at TK Kristen GMIT Koinonia Kupang. This research is a type of correlational research with a quantitative approach. Data was collected using a questionnaire and observation. The questionnaire for the role of parents was filled out by parents who had children aged 5-6 years at TK Kristen GMIT Koinonia Kupang and observations of children's polite behavior were filled out by researchers when making observations. This research was conducted at TK Kristen GMIT Koinonia Kupang g from February 4 to 22 March 2021. The population in this study were 33 parents and 33 children. Samples were taken from the entire population, namely 33 parents and 33 children. Data analysis techniques include prerequisite analysis, namely the normality test, linearity test and hypothesis testing. The data is tested using SPSS 16.0. The data collection tool used is a Likert scale. The results of correlation data analysis at a significant level of 5% obtained the results of rcount > rtable, namely 0.742 > 0.344. Based on the results of the hypothesis test, it can be concluded that there is a positive and significant relationship between the role of parents and the polite behavior of early childhood at TK Kristen GMIT Koinonia Kupang.